Qex: Symbolic SQL Query Explorer - Veanes, Margus; Tillmann, Nikolai; Halleux, Jonathan "Peli" de (LPAR-16, 2010)
We describe a technique and a tool called Qex for generating input tables and parameter values for a given parameterized SQL query. The evaluation semantics of an SQL query is translated into a specific background theory for a satisfiability modulo theories (SMT) solver as a set of equational axioms. Symbolic evaluation of a goal formula together with the background theory yields a model from which concrete tables and values are extracted. We use the SMT solver Z3 in the concrete implementation of Qex and provide an evaluation of its performance.